Framework Fluxionality of Organometallic Oxides : Synthesis, Crystal Structure, EXAFS, and DFT Studies on [{Ru(η6-arene)}4Mo4O16] Complexes - Laurencin, Danielle; Fidalgo, Eva Garcia; Villanneau, Richard; Villain, Françoise; Herson, Patrick; Pacifico, Jessica; Stoeckli-Evans, Helen; Bénard, Marc; Rohmer, Marie-Madeleine; Süss-Fink, Georg; Proust, Anna (My University, 2003)
Reactions of the molybdates Na2MoO4•2 H2O and (nBu4N)2[Mo2O7] with [{Ru(arene)Cl2}2] (arene=C6H5CH3, 1,3,5-C6H3(CH3)3, 1,2,4,5-C6H2(CH3)4) in water or organic solvents led to formation of the triple-cubane organometallic oxides [{Ru(η6-arene)}4Mo4O16], whose crystal and molecular structures were determined. Refluxing triple cubane [{Ru(η6-C6H5CH3)}4Mo4O16] in methanol caused partial isomerization to the windmill form. The two isomers of [{Ru(η6-C6H5CH3)}4Mo4O16] were characterized by Raman and Mo K-edge X-ray absorption spectroscopy (XAS), both in the solid-state and in solution. This triple-cubane isomer was also used as a spectroscopic model to account for isomerization of the p-cymene windmill [{Ru(η6-1,4-CH3C6H4CH(CH3)2)}4Mo4O16] in solution. Using both Raman and XAS techniques, we were then able to determine the ratio between the windmill and triple-cubane isomers in dichloromethane and in chloroform. Density functional calculations on [{Ru(η6-arene)}4Mo4O16] (arene=C6H6, C6H5CH3, 1,3,5-C6H3(CH3)3, 1,4-CH3C6H4CH(CH3)2, C6(CH3)6) suggest that the windmill form is intrinsically more stable, provided the complexes are assumed to be isolated. Intramolecular electrostatic interactions and steric bulk induced by substituted arenes were found to modulate but not to reverse the energy difference between the isomers. The stability of the triple-cubane isomers should therefore be accounted for by effects of the surroundings that induce a shift in the energy balance between both forms.
Keywords: density functional calculations; EXAFS spectroscopy; fluxionality; organometallic oxides; polyoxometalates